2020
DOI: 10.3390/polym12030621
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer Copper-Zinc Alloy Particles-Reinforced Wood Plastic Composites with High Gloss and Antibacterial Properties for 3D Printing

Abstract: In this work, micrometer copper-zinc alloy particles-reinforced particleboard wood flour/poly (lactic acid) (mCu-Zn/PWF/PLA) wood plastic composites with high gloss and antibacterial properties for 3D printing were prepared by a melt blending process. The structure and properties of the composites with different contents of mCu-Zn were analyzed by means of mechanical testing, dynamic mechanical analysis, thermogravimetric analysis, differential scanning calorimetry, X-ray diffraction, scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…However, introducing PWF into PLA does not produce a glossy appearance or antibacterial properties. Therefore, micrometer copper–zinc (mCu–Zn) alloys have been introduced [ 51 ]. First, PWF was treated with hydrogen peroxide under alkaline conditions to remove cellulose, which may degrade at high processing temperatures and cause the material to discolor or lose strength [ 51 ].…”
Section: Metal-based Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, introducing PWF into PLA does not produce a glossy appearance or antibacterial properties. Therefore, micrometer copper–zinc (mCu–Zn) alloys have been introduced [ 51 ]. First, PWF was treated with hydrogen peroxide under alkaline conditions to remove cellulose, which may degrade at high processing temperatures and cause the material to discolor or lose strength [ 51 ].…”
Section: Metal-based Additivesmentioning
confidence: 99%
“…Therefore, micrometer copper–zinc (mCu–Zn) alloys have been introduced [ 51 ]. First, PWF was treated with hydrogen peroxide under alkaline conditions to remove cellulose, which may degrade at high processing temperatures and cause the material to discolor or lose strength [ 51 ]. Maximum mechanical properties occurred when 5 wt % PWF was introduced into the PLA matrix.…”
Section: Metal-based Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, objects associated with public use can be made safer by 3D printing with antimicrobial nanocomposites. Yang et al (2020) fabricated a particleboard wood flour/PLA composite filament reinforced by copper-zinc alloy nanoparticles for FDM-based 3D printing. They suggested that the developed filament can be used to print personalized furniture, public benches and toys, owing to its good antimicrobial properties and environmental safety (Yang et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…Yang et al (2020) fabricated a particleboard wood flour/PLA composite filament reinforced by copper-zinc alloy nanoparticles for FDM-based 3D printing. They suggested that the developed filament can be used to print personalized furniture, public benches and toys, owing to its good antimicrobial properties and environmental safety (Yang et al, 2020). In short, these examples provide a clear vision of how 3D printing of antimicrobial nanocomposites can be applied to make imaginative and customized products.…”
Section: Applicationsmentioning
confidence: 99%